Temperature Distribution of Frozen Wall Formed by Irregular Hole Arrangement During In Situ Repair of Underground Shield Machine - Rongjian Shi; Caihong Long; Zequn Hong; Yelei Qian (Applied Sciences)
In order to study the development law of the irregular hole freezing temperature field, combined with the shield solution project of the Nanjing Water Supply Corridor, the distribution characteristics and influencing factors of the irregular freezing temperature field of the river bottom shield machine are studied by numerical simulation. The following conclusions are obtained: (1) The extension length of the outer ring pipe is correlated approximately positively with the thickness and average temperature of the freezing wall at the bottom of the cup. The thickness increases by 0.25 m, and the average temperature decreases by 1.25 °C for every 1 m increase in the extension length. (2) The intersection time decreases logarithmically with the increase in the extension length of the outer ring tube. (3) As the ratio of the axial angle between the two adjacent tubes in the weak area of the outer ring tube becomes larger, the temperature of the weak point in the center of the two tubes increases approximately linearly. The midpoint temperature of the two tubes increases by 3.3 °C for every 1 increase in the angle coefficient. (4) With the increase in the opening angle of the inner ring hole, the thickness and average temperature change, respectively, at 150 d are not more than 0.15 m and 0.6 °C. The results show that under the irregular freezing form, the angle and length of the outer ring pipe have a great influence on the temperature field, and the angle of the inner ring pipe has little influence on the final distribution of the temperature field. The average temperature and the temperature distribution of the weak points show a trend of decreasing first and then increasing along the shield advancing direction, reaching a minimum near the cutterhead.